94.7k views
16 votes
Find x - and - y intercepts of the following equation. a. 4x - 3y = 12 b. y = 1/3x c. y = 2x + 5 d. y = 6



User Kazy
by
4.6k points

1 Answer

5 votes

✒️ Equation

••••••••••••••••••••••••••••••••••••••

A. To find the x - intercept, let y = 0.


\tt \: \: \large \tt \: \begin{array}c \hline \tt \: 4x \: - \: 3y \: = \: \tt\underline{\green{ 12 }} \\ \tt 4x \: - \: 3(0) \: = \: \tt\underline{\blue{ 12 }} \\ \tt4x \: - \: 0 \: = \: \tt\underline{\pink{ 12 }} \\ \tt \tt\underline{\red{ \: x \: = \: 3 }} \\ \\ \tt \: x ↬\: the \: intercept\\ \tt\\ \hline\end{array} \: \\


\\

To find the y - intercept, let x = 0


\large \tt \: \begin{array} \hline \tt 4x \: - \: 3y \: = \: \tt\underline{\green{ 12 }} \\ \tt 4(0) \: - \: 3y \: = \: \tt\underline{\blue{ 12 }} \\ \tt \: 0 \: - \: 3y \: = \: \tt\underline{\pink{ 12 }} \\ \tt \tt\underline{\red{ y \: = \: - 4 }} \\ \\ \tt \: x ↬\: the \: intercept \\ \ \\ \hline\end{array} \:


\\

B. Replace x with 0 and solve for y. Then replace y with 0 and solve for x.


\large \tt \: \begin{array}c \hline \tt y \: - \: intercept: \: y \: = \: (1)/(3)(0) \\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \tt = \tt\underline{\red{ 0 }} \\ \\ \tt \: x \: and \: y ↬ intercepts: (0,0)\\ \\ \tt \: x \: ↬ \: intercepts: \: 0 = \: (1)/(3) x \\ \quad\quad \quad \quad\quad\quad\quad\quad\quad \: \tt \tt\underline{\red{ \: 0 \: = \: x }} \ \\ \\ \hline\end{array} \\


\\

The equation in b is a linear equation in the form y = mx, where m is any real number. the graph of any equation in the form y = mx is always a line that passes through the origin, which means that both the x - and - y - intercepts are (0,0).


\large \tt \: \begin{array} \hline \tt intercept \: for \: m \: of \: y \: = \: \tt\underline{\red{ mx }} \\ \hline\end{array}


\\

C. Replace y with 0, then solve for the x.


\large \tt \: \begin{array}c \hline \tt x ↬ \: intercept : \: 0 \: = \: 2x \: \ + 5 \\ \\ \tt - 5 \: = \: 2x\\ \\ \tt \: ( - 5)/(2) \: = \: x\\ \\ \tt \: x \: ↬ \: intercept \ \\ \hline\end{array}

Now, replace x with 0, and then solve for y.


\large \tt \: \begin{array} \hline \tt y ↬ \: intercept: \: y \: = \: 2(0) \: + \: 5 \\ \\ \tt \: y \: = \: 0 \: + \: 5 \\ \\ \tt \: y \: = \: 5 \\ \\ \tt y ↬ \: intercept \ \\ \\ \hline\end{array}

The equation in 11c is written in the form y = mx + b. note than in the form, when x is replaced by 0 to find the y↬intercept. you are left with the constant b.


\large \tt \: \begin{array} \hline \tt \: the \: y ↬ intercept \: of \: y \: = \: mx \: + \: b \\ \hline\end{array}

If the equation is in the form y = mx + b, where m and b are real numbers, then the y ↬intercept is b.


\\

D. Remember that the graph of y = 6 is horizontally line parallel to the x axis that passes through the y axis at (0,6). since the line is parallel to x axis, it will not incest tha x-axis. Hence, there is no x ↬ intercept.


\\ \\ \\


\pmb{(ノ‥)ノ}\qquad\qquad\qquad\qquad\boxed{\tt{[05-12-2022]}} \\ \qquad\qquad\qquad\qquad\qquad\qquad\boxed{\tt{[03:11 \: am]}}